Geothermal Gradient Estimation and Geothermal Energy Potentiality of Oil Wells in Oilfields - Ahmed A. Mohammed; Farag A. Ali; Ibrahim M. Abou El Leil (African Journal of Advanced Pure and Applied Sciences, 2024)
Many applications in oilfields require knowledge of the geothermal gradient. The purpose of this study is to assess the potential of oil wells as sources of geothermal energy by determining the geothermal gradient present in rock formations. In the Gialo 59E oil field, bottom hole temperature (BHT) data from twelve wells were gathered to determine the trend of the geothermal gradient across different rock formations. Regional geothermal gradients differ substantially between wells and at different depths. The average temperature is approximately 2.9°C/100 m, with a range of 2.25–3.19°C. Notably, the depth and sedimentary column thickness affect the geothermal gradient. The geothermal gradient and depth of the many wells under investigation in different formations are generally correlated. Given the kind of rock, its specific heat, and heat transport, the quantity of geothermal gradient is undoubtedly significant. The average depth was 643.30–945.73 m, and the observed bottom hole temperatures, which ranged from 144–195°C, were 802.65 m and 168.42°C, respectively, for each of the twelve wells. The temperature increases with depth, according to the recorded bottom hole temperatures. The quantity of the water cut indicated the possibility of using these wells as a source of geothermal energy in power plants for the production of electricity. It may also be categorized as a source of low and medium enthalpy.